Transcriptomic analysis of nitrogen starvation- and cultivar-specific leaf senescence in winter oilseed rape (Brassica napus L.). (April 2015) - Koeslin-Findeklee, Fabian; Rizi, Vajiheh Safavi; Becker, Martin A.; Parra-Londono, Sebastian; Arif, Muhammad; Balazadeh, Salma; Mueller-Roeber, Bernd; Kunze, Reinhard; Horst, Walter J.
Highlights: Nitrogen efficiency of oilseed rape cultivars is related to delayed leaf senescence. Global analysis of gene expression in leaves revealed an N starvation-specific program. The pattern of N starvation-specific gene expression differed between early and late senescing cultivars. Six marker genes for cultivar-specific late leaf senescence were identified. Abstract: High nitrogen (N) efficiency, characterized by high grain yield under N limitation, is an important agricultural trait in Brassica napus L. cultivars related to delayed senescence of older leaves during reproductive growth (a syndrome called stay-green). The aim of this study was thus to identify genes whose expression is specifically altered during N starvation-induced leaf senescence and that can be used as markers to distinguish cultivars at early stages of senescence prior to chlorophyll loss. To this end, the transcriptomes of leaves of two B. napus cultivars differing in stay-green characteristics and N efficiency were analyzed 4 days after the induction of senescence by either N starvation, leaf shading or detaching. In addition to N metabolism genes, N starvation mostly (and specifically) repressed genes related to photosynthesis, photorespiration and cell-wall structure, while genes related to mitochondrial electron transport and flavonoid biosynthesis were predominately up-regulated. A kinetic study over a period of 12 days with four B. napus cultivars differing in their stay-green characteristics confirmed the cultivar-specific regulation of six genes in agreement with their senescence behavior: the senescence regulator ANAC029, the anthocyanin synthesis-related genes ANS and DFR-like1, the ammonium transporter AMT1;4, the ureide transporter UPS5, and SPS1 involved in sucrose biosynthesis. The identified genes represent markers for the detection of cultivar-specific differences in N starvation-induced leaf senescence and can thus be employed as valuable tools in B. napus breeding.